Pemanfaatan Komoditas Tomat (Lycopersicum esculentum Mill) Guna Menciptakan Nilai Tambah Dengan Melakukan Sosialisasi Pembuatan Manisan Tomat Di Desa Paok Pampang Kecamatan Sukamulia Lombok Timur - Ahmad Jupri; Suripto Suripto; Salsa Billah; Tapaul Rozi; Eka Sunarwidhi Prasedya; Nurul Hidayah (Jurnal Gema Ngabdi, 2023)
Tomato (Lycopersicum esculentum Mill) is a horticultural crop that has high economic value and is widely used as a commercial product. Abundant tomato harvests make the price of tomatoes in Paok Pampang Village cheap. It was recorded that in July 2023, tomatoes have decreased in price from IDR 12,000 – IDR 22,000, down to IDR 3000 – IDR 4000 per kilo. With this low price, farmers sometimes leave their tomatoes in their fields, causing tomatoes that are ready to be harvested to rot and waste. The method used in this activity is a method in the form of practice that is carried out with several stages, including Activity Planning, Activity Preparation, and Activity Implementation. Next is the socialization of candied tomato products. This socialization aims to educate the public that tomatoes can have added value if converted into new products such as processed into candied tomatoes. The people of Paok Pampang Village are also enthusiastic about this candied tomato product. This can be seen through the questions raised during the socialization process